Tato dan Risiko Komplikasinya - Putri, Putu Ayu Krisna Cahyaning; Saraswati, Putu Dyah Ayu (Cermin Dunia Kedokteran, 2025)
Tattoos are a form of body modification that involves inserting indelible ink into the dermis to alter skin pigmentation. Based on the duration of pigment retention, tattoos are classified into two types: temporary tattoos and permanent tattoos. The increase in the prevalence of tattooing has raised awareness of the adverse reactions associated with tattoos, which are not limited to the risk of dermatological complications, but also systemic complications. Adverse reactions related to tattoos are classified into infection, inflammatory, and neoplastic complications. Risks of infection and neoplasia are only observed in permanent tattoos. Hypersensitivity reactions to tattoo pigments are the most common adverse effects for both permanent and temporary tattoos. Risk of infection during permanent tattooing varies based on the causative pathogens, which may include bacterial, viral, fungal, and parasitic infections, manifesting as both localized and systemic issues. Adverse reactions have also been reported in relation to the pigment colors used in tattoos, suggesting that certain pigment components may be associated with harmful effects. A standardized regulatory framework is necessary to ensure the safety of tattoo inks and to prevent adverse health outcomes.